Ultrasound-Guided Percutaneous Drainage of Iliopsoas Abscess With Septicemia in an Adolescent: A Case Report and Literature Review - Jiang, Kun; Zhang, Wenxiao; Fu, Guoyong; Cui, Guanghe; Li, Xuna; Ren, Shousong; Fu, Tingliang; Geng, Lei (Frontiers in Surgery, 2022)
Introduction: Iliopsoas abscess with septicemia in the pediatric population is rare. Early diagnosis and effective management of this emergent disorder remain challenging for clinicians. Case Presentation: A 14-year-old girl presented with right lateral and posterior hip pain and fever for 7 days before admission. Blood culture was positive for Staphylococcus aureus. Enhanced magnetic resonance imaging revealed abscesses located in the right iliopsoas muscle and on the surface deep to the fascia of the right sacroiliac joint that were 6.8 cm × 6.2 cm × 5.7 cm and 3.7 cm × 3.5 cm × 2.1 cm, respectively. A diagnosis of right iliopsoas abscesses with septicemia was made. The patient received intravenous antibiotics, underwent ultrasound-guided percutaneous catheter drainage, and recovered uneventfully. Medical literature regarding this issue published in English language during the last two decades was reviewed. Discussion: Primary synchronous psoas and iliacus muscle abscesses are rare and emergent disorder in the pediatric age group. The diagnosis is generally delayed owing to the deep anatomic location and nonspecific signs and symptoms. A comprehensive medical history, meticulous physical examination, and judicious use of imaging studies could establish the timely and accurate diagnosis. Surgeons should be aware of the occurrence of multiple abscesses. Prompt and adequate antibiotic therapy accompanied by mini-invasive approach, such as ultrasound-guided, laparoscopic or video-retroperitoneoscopic drainage of the infectious focus, if indicated and feasible, is important to achieve good outcome in the management of iliopsoas abscess. Keywords: iliopsoas abscess; Staphylococcus aureus; ultrasonography; percutaneous catheter drainage; pediatrics